Sound Design Composition Of ISI Padangpanjang with Studio one 5 Application - Gulo, Yogi; Zaidi, Ahmad; Rahmadinata, Melisa Fitri; Munafri, Sastra; Hendri, Yon (Institut Seni Indonesia Padangpanjang, 2025)
The sound composition of the Indonesian Institute of the Arts Padang Panjang with the Studio One 5 Application is a process of creating musical works using digital technology. This musical composition originates from the activities of the academic community that took place in the environment of the Indonesian Institute of the Arts Padang Panjang. The Studio One 5 application is used as a tool to process sounds taken from art education activities, then processed in a demicrophone manner to become a new sound composition. This composition was created with the aim of describing the atmosphere in the environment of the Indonesian Institute of the Arts Padang Panjang which is presented through audio sound. The method of creating the sound composition of the Indonesian Institute of the Arts Padang Panjang involves modern music production techniques. The stages of creation are by recording audio samples which are then processed through the Studio One 5 application, and given additions such as the use of sound effects, mixing, and digital mastering. After the entire music work is complete, the musical composition that originates from the sounds in the environment of the Indonesian Institute of the Arts Padang Panjang then becomes a new musical composition entitled sound design isi padangpanjang.